First Karyotype Report of Arum cyrenaicum Hruby (Araceae) from AL-Jabal AL-Akhdar, Libya. - A. Bashasha, Jamila; F. Imryed, Yousif; J. Adam, Halima (Scientific Journal of University of Benghazi, 2025)
In this paper, somatic chromosome number and karyotype of the endemic species Arum cyrenaicum Hruby (Araceae), collected from the Tolmitha site in the Al-Jabal Al-Akhdar region of Libya, are reported for the first time. Our results revealed that all the studied populations were polyploid ( 2n=4x=56) with a karyotype formula (KF) of 6M+38m+10sm+2st(2SAT). Furthermore, the chromosome size of A. cyrenaicum was medium to small-sized, with lengths ranging from the largest 4.72±.21μm to the smallest 2.88±.04μm. According to Stebbins’ karyotype asymmetry classification, it was 1A type (symmetrical one). Satellites were observed on two chromosome pairs. The karyotypes of these species’ findings contribute to the scientific understanding of this plant from a genetic perspective study. In addition to taxonomic characters, the analyzed karyotype features will contribute to the characterization of A. cyrenaicum varieties and to establish a base for future research.